2013
DOI: 10.1080/15564894.2012.761299
|View full text |Cite
|
Sign up to set email alerts
|

DNA and Pacific Commensal Models: Applications, Construction, Limitations, and Future Prospects

Abstract: Components of the Pacific transported landscape have been used as proxies to trace the prehistoric movement of humans across the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 120 publications
0
29
0
Order By: Relevance
“…Understanding from where, when, and how ancestral Austronesians bridged the unprecedentedly broad water gaps of the Pacific is a fascinating and yet contentious subject in anthropology (1)(2)(3)(4)(5)(6)(7)(8). Linguistic, archaeological, and genetic studies have demonstrated the complex nature of the process, where different components that helped to shape Lapita culture in Near Oceania each have their own unique history (1)(2)(3).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Understanding from where, when, and how ancestral Austronesians bridged the unprecedentedly broad water gaps of the Pacific is a fascinating and yet contentious subject in anthropology (1)(2)(3)(4)(5)(6)(7)(8). Linguistic, archaeological, and genetic studies have demonstrated the complex nature of the process, where different components that helped to shape Lapita culture in Near Oceania each have their own unique history (1)(2)(3).…”
mentioning
confidence: 99%
“…Given their close association to and dependence on humans for their dispersal, phylogeographic analyses of these commensal species provide unique insights into the complexities of Austronesian expansion and migrations (6,8,17). This "commensal Significance Paper mulberry, a common East Asian tree used for paper making, is propagated across the Pacific for making barkcloth, a practical and symbolic component of Austronesian material culture.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In Table 1, we give a summary of all modern and ancient commensal animal genetic data for four taxa: rat (Rattus exulans), pig (Sus scrofa), chicken (Gallus gallus), and dog (Canis lupus fimiliaris) (after [43], with additions from [44,45]). There is clearly far more coverage for Melanesia and Eastern Polynesia, the two spatial-temporal endpoints of the dispersal of people in to Polynesia.…”
Section: Chronology Of Settlement Of Western Polynesiamentioning
confidence: 99%